2006
DOI: 10.1002/ijc.21981
|View full text |Cite
|
Sign up to set email alerts
|

Interference with O‐glycosylation in RMA lymphoma cells leads to a reduced in vivo growth of the tumor

Abstract: Carbohydrate processing in cancer cells can influence the growth, metastatic potential, vascularization and immune recognition of such cells. Interference with N‐glycosylation has been shown both to reduce the membrane expression of MHC class I and to increase the in vitro sensitivity of tumor cells to NK cell killing. We investigated the effect of O‐glycosylation inhibition on the in vivo growth, phenotype and NK sensitivity of RMA lymphoma cells using benzyl N‐acetyl‐α‐D‐galactosamide (BAG). BAG‐treated cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…RMA-S cells, which have reduced MHC class I expression, are sensitive to NK killing, while the parental RMA cells form tumors in wild-type animals (24). In initial experiments, RMA-S cells formed tumor masses in NK cell-depleted wildtype animals (25), but not wild-type or ST8Sia IV Ϫ/Ϫ mice.…”
Section: St8sia IV ϫ/ϫ Mice Exhibit Exaggerated Contact Hypersensitivmentioning
confidence: 99%
“…RMA-S cells, which have reduced MHC class I expression, are sensitive to NK killing, while the parental RMA cells form tumors in wild-type animals (24). In initial experiments, RMA-S cells formed tumor masses in NK cell-depleted wildtype animals (25), but not wild-type or ST8Sia IV Ϫ/Ϫ mice.…”
Section: St8sia IV ϫ/ϫ Mice Exhibit Exaggerated Contact Hypersensitivmentioning
confidence: 99%
“…Swainsonine, in particular, is interesting, as it inhibits the formation of N -linked complex oligosaccharides with this inhibition correlative with enhancement with NK cell function. Consequently, inhibitors of N -, as well as O -linked glycosylation need to be expanded, because they should be useful for the treatment of cancer by effectively resetting NK functional activity by disruption of negative signals; given that inhibitors can be specifically targeted to tumor tissue [ 144 ]. More recently, it was shown that glycosylation regulates NK cell-mediated effector function through the PI3K pathway [ 132 ].…”
Section: Innate Recognition Of Glycans That Lends To Tumor Suppresmentioning
confidence: 99%